PORTRAIT OF RELIGIOUS FUNDAMENTALISM AMONG STUDENTS OF THE STUDY PROGRAM ISLAMIC EDUCATION - Dewi, Putri (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2022)
The term fundamentalism is often associated with extreme attitudes, rigidity, conservativeness, stagnation, conservativeness, and resistance to progress, so that many people shy away from the labeling of the term. Avoiding the use of non-neutral terms as above, in this study the term fundamentalism will be returned to its basic meaning, namely returning to religion in a